Estimates of Some Operators on One-Sided Weighted Morrey Spaces. (24th November 2013) - Shi, Shaoguang; Fu, Zunwei
Abstract : A version of one-sided weighted Morrey space is introduced. The boundedness of some classical one-sided operators in harmonic analysis and PDE on these spaces are discussed, including the Riemann-Liouville fractional integral.